The effect of network externalities on the perception of a new service offering mobile banking - Ewe, Soo Yeong *; Yap, Sheau Fen; Lee, Christina Kwai Choi (2012)
This study extends previous research by determining if potential adopters' perception of innovation characteristics mediates the effects of network externalities towards their intention to use mobile banking. The study also explores the possible moderating effects of technology anxiety between network externalities, innovation characteristics and intention to use mobile banking